Get Out and Stay Out: New Insights Into DNA Methylation Reprogramming in Mammals - Greenberg, Maxim V. C. (Frontiers in Cell and Developmental Biology, 2021)
Vertebrate genomes are marked by notably high levels of 5-cytosine DNA methylation (5meC). The clearest function of DNA methylation among members of the subphylum is repression of potentially deleterious transposable elements (TEs). However, enrichment in the bodies of protein coding genes and pericentromeric heterochromatin indicate an important role for 5meC in those genomic compartments as well. Impaired function of major components of DNA methylation machinery results in lethality in fish (Rai et al., 2006; Anderson et al., 2009), amphibians (Stancheva et al., 2001) and mammals (Li et al., 1992; Okano et al., 1999). In eutherian mammals, DNA methylation has a more diversified—or at least more well-studied—set of functions, including maintaining X inactivation, imprinting, and silencing of germline-specific genes. Despite, or perhaps because of, these functions, mammals exhibit a dramatic loss and regain of DNA methylation in early embryogenesis prior to implantation, and then again in the cells specified for the germline. In this minireview we will highlight recent studies that shine light on two major aspects of embryonic DNA methylation reprogramming: 1) The mechanism of DNA methylation loss after fertilization and 2) the protection of discrete loci from ectopic DNA methylation deposition during reestablishment. Finally, we will conclude with some extrapolations for the evolutionary underpinnings of such extraordinary events that seemingly put the genome under unnecessary risk during a particularly vulnerable window of development.